Optimalisasi Pengelolaan Laboratorium IPA Melalui Workshop Development Management of Laboratory Di SMPN 33 Makassar - Faisal; Hartono; Andi Rahmat Saleh; Sitti Saenab; Hamka L. (Ininnawa : Jurnal Pengabdian Masyarakat, 2025)
The use of laboratories in science learning plays a crucial role in enhancing students' skills and understanding. However, at UPT SPF SMP Negeri 33 Makassar, the science laboratory has not been utilized optimally. The main inhibiting factor is the lack of understanding among teachers and laboratory assistants in managing and using laboratory equipment. To address this issue, the "Workshop Development Management of Laboratory" was conducted with the aim of improving teachers' and laboratory assistants' skills in laboratory management. The methods used included training, the development of Standard Operating Procedures (SOP), and an evaluation of the workshop's effectiveness. The results of this activity showed an increase in participants' understanding and skills, with an average satisfaction rate of 89%. The implementation of the established SOP is also expected to enhance the laboratory’s effectiveness in supporting science learning.